2011
DOI: 10.1097/mpg.0b013e31821f9b85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus rhamnosus Strain GG in Pediatric Obesity‐related Liver Disease

Abstract: Probiotic L rhamnosus strain GG warrants consideration as a therapeutic tool to treat hypertransaminasemia in hepatopathic obese children noncompliant with lifestyle interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
199
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(214 citation statements)
references
References 30 publications
6
199
1
8
Order By: Relevance
“…A double blind, placebo-controlled pilot study, on obese children showed that supplementation with probiotics showed no alteration in ultrasound liver parameters (27). In the current study, Ahmad Shavakhi et al reported that probiotics combined with Metformin decreased ultrasound grading of NASH significantly better than metformin alone in patients with NASH (41).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A double blind, placebo-controlled pilot study, on obese children showed that supplementation with probiotics showed no alteration in ultrasound liver parameters (27). In the current study, Ahmad Shavakhi et al reported that probiotics combined with Metformin decreased ultrasound grading of NASH significantly better than metformin alone in patients with NASH (41).…”
Section: Discussionmentioning
confidence: 49%
“…Our results with regards to reductions in liver aminotransferase are similar to those of Nabavi et al (26), who showed that probiotic yogurt for 8 weeks in patients with NAFLD caused a decrease in ALT and AST. In another study, probiotic supplementation in pediatric obesity-related liver disease for 8 weeks decreased ALT serum level (27). Also, a meta analysis study in 2016 reviewed efficacy of probiotics in nonalcoholic fatty liver disease in adult and children, in which a total of 9 clinical trial studies were included and reported significant differences in ALT, AST, and BMI between the 2 childhood groups (28).…”
Section: Discussionmentioning
confidence: 99%
“…In an RCT performed by Vajro et al on obese children treated with Lactobacillus GG for 8 weeks, a significant decrease in ALT was reported (34). In RCT of VSL#3, "a mixture of eight probiotic strains" compare to placebo in overweight children with biopsy-proven NAFLD, administration of VSL#3 for 4 months significantly improves NAFLD in children (27).…”
Section: Discussionmentioning
confidence: 98%
“…They found that 4-month supplement of VSL#3 significantly improved the liver function and increased GLP-1/ aGLP1 levels suggesting the beneficial effects of VSL#3 might be GLP-1-dependent [104]. Similarly, consistently beneficial effects were also observed on children with obesity and NAFLD by administering probiotics such as Lactobacillus rhamnosus strain GG [105] and mixed bacteria of Lactobacillus bulgaricus and Streptococcus thermophilus [106]. Sepideh, A et al investigated the effects of a multistrain probiotic supplementation in NAFLD patients in a RCT study [107], and the results showed dramatic improvement in insulin sensitivity and inflammation.…”
Section: Gut Microbiota-targeted Therapies Of Nafldmentioning
confidence: 97%